Virtual Patients in Clinician’s Education: Theory, Knowledge and Self-efficacy in Anxiety Diagnosis - Calinici, Simona Mirela; Calinici, Tudor; Miclea, Mircea (International Journal of Online and Biomedical Engineering (iJOE), 2017)
The paper aims to investigate the extent to which the use of virtual patient (VP) improves the level of theoretical knowledge and students’ confidence (self-efficacy) of psychology and medicine students to perform clinical diagnostic. We created two classes on an e-learning Moodle platform, presenting, as virtual patient, the evaluation of the same panic disorder case. One class uses a linear VP , the other, a branched VP (a decisional tree type). The sample consisted of 159 volunteer participants, psychology and medicine students, randomly assigned to one of three conditions : control, linear virtual patient ( PVL) and branched virtual patient (PAD). Before and after the training with the virtual patient sequence, a questionnaire investigates the theoretical knowledge and the self-efficacy levels. For self-efficacy evaluation we used the Session Management sub-scale of Counsellor Activity Self-Efficacy Scales, by Robert W. and Clara E. Hill. Both types of VPs are associated with a statistically significant increase of knowledge about panic disorder diagnostic criteria, reinforcing the fact that the virtual patient has an impact on the cognitive profile (declarative knowledge) and on self-efficacy (related to procedural knowledge). Still, the study does not prove that one of the two types of virtual patient has a significant better outcome .